Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1979
DOI: 10.1159/000115103
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Nucleotides in Progressive Muscular Dystrophy

Abstract: The authors radioimmunoassayed cyclic nucleotide concentrations in plasma and biopsied muscles of muscular dystrophy and muscles of chicken embryo. c-AMP concentrations in plasma were significantly lowered in Duchenne-type muscular dystrophy and this lowered degree was correlated with the stage of progression. Plasma c-GMP levels were also depressed in Duchenne-type dystrophy. In biopsied muscles, c-AMP concentrations per milligram of non-collagen protein were within normal limits. Therefore, the decrease of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Sildenafil also significantly reduces exerciseinduced ischemia (33), a potentially important pathogenetic mechanism in dystrophin-deficient skeletal muscle (10,34). In fact, defects in cGMP signaling are also suggested from studies in dystrophin-deficient skeletal muscle (35,36), and recently, Asai et al (37) showed that treatment with tadalafil, another known PDE5 inhibitor, ameliorates contraction-induced skeletal muscle damage. Finally, sildenafil can cross the blood-brain barrier to inhibit brain PDE5A (38), which could theoretically affect sympathetic and parasympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%
“…Sildenafil also significantly reduces exerciseinduced ischemia (33), a potentially important pathogenetic mechanism in dystrophin-deficient skeletal muscle (10,34). In fact, defects in cGMP signaling are also suggested from studies in dystrophin-deficient skeletal muscle (35,36), and recently, Asai et al (37) showed that treatment with tadalafil, another known PDE5 inhibitor, ameliorates contraction-induced skeletal muscle damage. Finally, sildenafil can cross the blood-brain barrier to inhibit brain PDE5A (38), which could theoretically affect sympathetic and parasympathetic outflow.…”
Section: Discussionmentioning
confidence: 99%